The interference of light waves for the course of physical optics; 10th International Technology, Education and Development Conference (INTED2016) - Sklyarova E. A. Elena Aleksandrovna; Semkina L. I. Lyudmila Iosifovna; Lider A. M. Andrey Markovich; Kudiyarov V. N. Victor Nikolaevich; Chudinova E. A. Ekaterina Aleksandrovna; Smekalina T. V. Tatiana Vladimirovna; Zagorskaya L. Yu. Lubov Yur'evna (2016, 2016)
Title screen